Fundraising Bagi Pemberdayaan Pendidikan pada Panti Asuhan Hafizhil Yatamu Kota Padangsidimpuan - Darliana Sormin; Samsidar Samsidar (IAIN Padangsidimpuan, 2019)
Fundraising is one of the main forms of funding sources for education expenses. Through fundraising, these educational institutions and community organizations will be helped in implementing the organization's vision and mission. Fundraising activity is to raise funds from the private sector and the community, especially for educational purposes. Fundraising is carried out because of the desire to meet the needs of institutions or organizations, funds that are desired by institutions and organizations can be obtained in many ways, as bazar, the students’ handicraft expo, service, micro business, social institution (as orphanage, nursing home, LSM), and Zakat Institution (as BAZNAS, LAZISMuh, Dompet Dhu’afa, Baitul Maal Mualamat)